Analisis penerapan keterampilan dasar mengajar guru pada mata pelajaran ppkn kelas VI sekolah dasar - Rizal Khoirul Huda; Hasan Mahfud; Matsuri Matsuri (Didaktika Dwija Indria, 2024)
Education plays a significant role in humans in living their lives. Every individual needs and has the right to undergo education. Education in Indonesia is carried out in stages starting from primary, secondary and tertiary levels. Basic education is held at the elementary school level. Considering that basic education has a significant position, the role of teachers who have good basic teaching skills is necessary. Therefore, researchers are interested in conducting research on the application of teachers' basic teaching skills in Civics subjects in class VI at SDN Genengsari 03. The research uses qualitative methods with a phenomenological approach. Data collection instruments consist of observation, interview, questionnaires and documentation. The research results showed that the application of teachers' basic teaching skills had been carried out well. In the first and second observations the teacher had implemented 29 of the 32 components or a percentage of 90.62%. In the third observation, the teacher implemented 31 components with a percentage of 96.87%.. Furthermore, in the interview instrument, the teacher answered the majority of questions well. One question about verbal reinforcement was not answered optimally by the teacher. In the questionnaire instrument, teachers have obtained an average percentage of skills implementation of more than 50% of each component. The obstacles experienced by teachers during implementation are the components of non-verbal reinforcement, variation, and problem expansion. The theoretical implication of this research is that teachers know the extent of their mastery of basic teaching skills. Meanwhile, the practical implication is that teachers can use the research instrument data to find out the extent to which basic teaching skills are implemented in class VI at SDN Genengsari 03.